Bandwagon effect, free-rider effect, tragedy of the commons: collaborative governance of marine pollution - Gu, Yu (Frontiers in Marine Science, 2025)
The issue of marine pollution is becoming one of the core challenges in global environmental protection, particularly when it comes to coordinating governance among nations and stakeholders. Problems such as uneven distribution of responsibilities and low efficiency of cooperation are frequently encountered. Traditional governance models struggle to effectively address the complexity of trans-regional and cross-sectoral pollution sources. In response, this paper uses the bandwagon effect, free-rider effect, and tragedy of the commons as theoretical frameworks, drawing on models and a large body of statistical data to explore strategies for collaborative governance of marine pollution. The results show that when the reputation and benefits gained from managing marine pollution are low, the governance by countries most reflects the tragedy of the commons. Otherwise, their governance best exemplifies the bandwagon effect.